ANALYSIS OF SPINNING RESERVE SETTINGS AGAINST ANTICIPATION OF BLACK OUT AND TOTAL FUEL USE AT POWER HOUSE DIVISION - Jhon Hericson Purba; Elsa Gultom (Program Studi Teknik Elektro Universitas Peradaban, 2023)
One of the biggest users of electrical energy in Batam City is the Batamindo Industrial Park area, so that area is required to have an electricity provider managed by the Batamindo Power House Division. To anticipate generation problems such as fuel gas trips in the power generation system, generation failures such as power disruption or even total blackouts, Power House Batamindo has a big responsibility. Power House Batamindo makes maximum and minimum power reserve limits. However, this can result in a large use of fuel for power generation and will also increase the cost of electricity production. In a converted generator engine, it will produce more power if it uses diesel fuel rather than gas. The results of research conducted for one month and data analysis carried out, as much as 84.7% of the installed spinning reserves are at 10-14 MW and as much as 5.1% are below the limit of the provision for spinning reserves (10-14 MW) which must be suppressed the numbers. The results of the research also prove that to prevent high diesel fuel emissions in generator engines, it is necessary to save diesel fuel by avoiding generation problems, one of which is paying the spinning reserve limit.